MOTIVASI MENGIKUTI EKSTRAKURIKULER KEAGAMAAN HUBUNGANNYA DENGAN AKHLAK DAN PRESTASI SISWA - Mohamad Yudiyanto; Rinda Fauzian (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2021)
Motivation to learn can determine student morals and achievement. Meanwhile, one of the phenomena that is important and interesting to research is the low motivation of students in participating in religious extracurricular activities at SMK Mutiara and SMK Muhammadiyah 2 Bandung. The research method used is a mixed method. Data were collected through observation, interviews, documentation and questionnaires. The data analysis used is preliminary analysis and hypothesis test analysis. The results showed (1) student motivation in participating in religious extracurricular activities at SMK Mutiara had a low level of relationship and at SMK Muhammadiyah 2 Bandung City had a high enough level of relationship, (2) SMK Mutiara and SMK Muhammadiyah 2 had a positive correlation. However, there are significant differences between the two, especially in terms of significance. The intensity of religious extracurricular activities at SMK Muhammadiyah 2 Bandung is more intense than the implementation of religious extracurricular activities at SMK Mutiara.